ANALISIS KETAHANAN PANGAN (TANAMAN PADI) PADA WILAYAH YANG TERKENA BANJIR DI KECAMATAN KRUENG SABEE KABUPATEN ACEH JAYA - Rika Fitri; Agussabti .; Safrida . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
The objective of the study was to analyze the food security of flood affected areas of Krueng Sabee sub-district of Aceh Jaya district and the factors affecting food security (rice crops) affected by floods. This research is using descriptive quantitative analytic method. Total sample was 75 respondents. As many as 60 respondents from 4 villages in Krueng Sabee Sub-district, Aceh Jaya District: 15 respondents from Panggong Village, 15 respondents from Buntha Village, 15 respondents from Desa Datar Luas and 15 respondents from Padang Datar Village and 15 respondents from related offices. Based on the results of the variables of food security (rice crops) affected by floods in Krueng Sabee Sub-district, Aceh Jaya District, the level of food security in the flood affected areas in Krueng Sabee District, Aceh Jaya Regency is high (determination value R = 99.8% and correlation of R2 = 99.5%). Furthermore, the results  of factors affecting food security (rice crops) in Krueng Sabee Sub-district of Aceh Jaya Regency are physical factors (X1), non-physical factors (X2) and supporting factors (X3), indicating that the dominantly influential factor is 1 ) supporting factors (X3) are (47%), 2) non-physical factors (X2), ie (29.4%), and 3) physical factors (X1) ie (20%).[Z1]  [Z1]Kurangi abstrak maksimal 200 kata